Is hepcidin related with anemia and bone mineral metabolism in children with non-dialysis chronic kidney disease? - (:unkn) unknown (TURKISH PEDIATRICS ASSOC, 2019)
Aim: Functional iron deficiency secondary to inflammation and increased serum hepcidin lead to erythropoietin-resistant anemia in children with chronic kidney disease. Vitamin D deficiency, parathyroid hormone, and phosphate can also participate in chronic inflammation and anemia. The aim of this study was to evaluate the association between hepcidin, bone mineral metabolism, and anemia in non-dialysis pediatric patients with chronic kidney disease. Material and Methods: Thirty-five patients with stage 2-4 chronic kidney disease and 35 healthy subjects were enrolled in the study. Serum creatinine, blood urea nitrogen, uric acid, C-reactive protein, interleukin-6, hepcidin, complete blood count, ferritin, calcium, phosphorus, parathyroid hormone, 25-hydroxyvitamin D, 1,25-dihydroxyvitamin D, and fibroblast growth factor-23 levels were compared between the groups. Results: Ferritin, C-reactive protein, interleukin-6, blood urea nitrogen, creatinine, uric acid levels, and percentages of reticulocytes were significantly higher than in the controls (p<0.05). The mean serum hepcidin levels in the chronic kidney disease and control groups were 9.6 +/- 5.2 (range, 2.15-25.3) and 9.7 +/- 4.3 (range, 3.4-22.2) ng/mL and were not significantly different in either group. There were no differences in terms of serum phosphorus, 25-hydroxyvitamin D, 1,25-dihydroxyvitamin D and fibroblast growth factor-23 levels between the groups (p>0.05). Serum hepcidin levels were not correlated with anemia parameters, serum fibroblast growth factor-23, phosphorus, uric acid, C-reactive protein, parathyroid hormone, and 25-hydroxyvitamin D levels (p>0.05). However, serum hepcidin levels were correlated with 1,25-dihydroxyvitamin D and interleukin-6 levels (p=0.013 and p=0.002, respectively). Conclusion: Serum hepcidin levels may not increase significantly in non-dialysis pediatric patients with chronic kidney disease despite high levels of inflammatory markers such as C-reactive protein and interleukin-6. The increase of serum hepcidin levels may be inhibited by effective treatment of anemia with iron supplementation and erythropoietin, and the treatment of secondary hyperparathyroidism with phosphate binders and the active form of vitamin D, which decrease serum parathyroid hormone and fibroblast growth factor-23 levels, and control inflammation to some extent.
Keywords: Anemia; children; chronic kidney disease; hepcidin; vitamin D; GROWTH-FACTOR 23; CHRONIC RENAL-INSUFFICIENCY; IRON-METABOLISM; INFLAMMATION